Two new species of Amanita (Amanitaceae, Agaricales) from Anhui Province, China - Chen, Meng-Lan; Gong, Yin-Ping; Mukjang, Nilita; Zheng, Yun-Fei; Luo, Xia (Phytotaxa, 2026)
Amanita species hold significant economic and ecological value due to their roles in nutrient cycling, medicinal properties, and ecological interactions. This study, based on morphological and phylogenetic analysis of five gene loci (nrLSU, ITS, RPB2, TEF1-α, and β-TUB), proposes two new species of Amanita, namely A. qimenensis and A. sufflava from Anhui Province, China. Amanita qimenensis, belongs to A. sect. Amidella, is characterized by its small basidiomata and white to dirty white stipe decorated with white to pale brown minute squamulose. Amanita sufflava belongs to A. sect. Vaginatae. is characterized by medium to large basidiomata with the blond pileus, which is usually yellowish brown to brown in the center but paler toward the margin. The study provides line drawings, detailed morphological descriptions, and comparisons with related taxa for two species. The discovery of these new species unveils the rich fungal diversity in Anhui Province and underscores the importance of further exploration and conservation of fungal resources.